2006
DOI: 10.1097/01.shk.0000209523.05249.27
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Filling Characteristics Are Not Impaired but Systolic Performance Was Augmented in the Early Hours of Experimental Endotoxemia in Humans

Abstract: This study was performed to determine whether endotoxemia causes diastolic cardiac dysfunction. Eleven healthy volunteers, 30 +/- 6 years of age, underwent comprehensive transthoracic echocardiographic assessment including two-dimensional, M-mode transmitral and tissue Doppler of systolic and diastolic function at baseline and at 3 and 5 h after intravenous administration of purified Escherichia coli endotoxin (4 ng/kg). Data were analyzed by analysis of variance; P values of less than 0.05 were considered sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…In these patients, all abnormalities recovered within 7 days after sepsis resolution. In contrast, Marthu et al [94] observed no diastolic dysfunction during a 5-hour endotoxin infusion in healthy volunteers. A recent study in which 262 patients with severe sepsis and septic shock were studied [95] showed that diastolic dysfunction was not only common but also that it represented a major predictor of mortality in this setting.…”
Section: Septic Cardiomyopathymentioning
confidence: 90%
“…In these patients, all abnormalities recovered within 7 days after sepsis resolution. In contrast, Marthu et al [94] observed no diastolic dysfunction during a 5-hour endotoxin infusion in healthy volunteers. A recent study in which 262 patients with severe sepsis and septic shock were studied [95] showed that diastolic dysfunction was not only common but also that it represented a major predictor of mortality in this setting.…”
Section: Septic Cardiomyopathymentioning
confidence: 90%
“…In patients with diastolic dysfunction prior to the SIMD, difficult weaning from mechanical ventilation and increased need for inotropic support could be predicted [43, 44]. Mathru and coworkers [45], in a case-control pilot study with a group of 11 young people (aged 30 ± 6 years), previously healthy and endotoxin-challenged volunteers who had not received empirical volume loading, despite stating that knowledge of diastolic function status could be very helpful to predict how a septic patient would respond to changes in preload, didn´t find statistically significant differences in diastolic function with the control group. The authors found significant increase in wave A and E/A ratio after-endotoxin infusion and no significant changes from baseline in the E wave (p <0.05).…”
Section: Diastolic Functionmentioning
confidence: 99%
“…The studies above clearly show that 4-6 ng kg -1 of LPS in healthy human subjects are able to induce a hyperdynamic state characterized by a tendency for hypotension, a markedly decreased SVR and elevated CO at constant (352,506) or decreased preload (322,326). As it will be discussed, contractility is increased (326) or unchanged at 3 hours (506), and, at 5 hours, unaltered (326) or depressed in the presence of volume loading (265,322,506).…”
Section: Hemodynamics After Endotoxin Administration In Healthy Humansmentioning
confidence: 77%
“…In terms of Guyton's equilibrium diagram, the increase of CO at constant or decreased C P observed in LPS-treated healthy volunteers (326,352,506) implies a change of both the functional properties of the systemic circulation and of the heart. In Figure 5 the equilibrium point before the LPS injection is point A corresponding to a CO of 5.5 L min -1 and a CVP of 5 mmHg.…”
Section: Effects Of Sepsis On Resistance Vesselsmentioning
confidence: 99%
See 1 more Smart Citation